Miller Fisher syndrome: a rare variant of Guillain-Barré syndrome - Bandeira, Luciana Pinto; Palaoro, Luize Giuri; Degenszajn, Jairo (Autopsy and Case Reports, 2012)
This report describes the case of a 39-year-old male patient who presented to the emergency room with complaints of impaired balance, diplopia, and nasal voice. The patient had a history of upper respiratory tract infection. The initial physical examination revealed ataxia, ophthalmoplegia, and areflexia, which are consistent with the classic triad of Miller Fisher syndrome, considered a benign variant of Guillain-Barré syndrome. The patient developed peripheral facial paralysis during hospitalization. He underwent a treatment with immunoglobulin for five days, resulting in near complete resolution of the ataxia. However, the ophthalmoplegia and areflexia persisted. He was discharged to outpatient follow-up.